A Systematic Review: Development of Literature Capacity in Elementary School - Niswi Mukarromah; Sugito; Rahayu Condro Mukti (Indonesian Journal Of Educational Research and Review, 2023)
Literacy is one of the basic needs in education, especially in 21st-century learning. Literacy skills are essential for elementary school students, making students literate and lifelong learning. The school literacy movement can be used to improve elementary school students' literacy skills. Therefore, this systematic review focuses on analyze the literacy movement in schools in developing literacy skills in elementary schools. The analysis was carried out based on the item review methodology by selecting articles for systematic review. A total of 15 selected articles discussing the development of literacy skills in elementary schools published from 2018 to 2022 were identified using the database from the publish or perish 8 software. The PRISMA 2020 methodology is used in the review. The five findings of the literacy movement can be obtained based on the results obtained through the synthesis of several articles by answering research questions. Implemented in elementary schools, namely (1) Literacy culture strategy, (2) Utilization of digital technology, (3) Procurement of reading books, (4) Development of library facilities and character building, and (5) Following the national assessment. Therefore, the impact of the findings of this article is to contribute to the organizers of the literacy movement in schools in developing students' literacy abilities in elementary schools.